Teachers' professional development (Hawthorn, Vic : Australian Council for Educational Research, 1991)
A reappraisal of professional development for teachers. Teacher development: achievements and challenges. The dependence of teacher development on teacher evaluation. Teacher development and the teacher. Teaching, teacher thinking and teacher development...
Keywords: Education; Australia; Teachers; Teachers -- In-service training -- Australia